211k views
1 vote
Can anyone tell me how to do this? (Steps) and can you answer these two questions for me plz

Need by tomorrow

Can anyone tell me how to do this? (Steps) and can you answer these two questions-example-1
User Gwen
by
6.4k points

1 Answer

2 votes
ax²+bx+c=0

The formula to solve for x is:


x= \frac{-b(+/-) \sqrt{ b^(2)-4ac } }{2a}


So for 3x²+13x+10=0, plug in the data

x=-13±√13²-4(3)(10) / 2(3)
x=-13±√169-120 / 6
x=-13±√49 /6
x=-13±7 / 6

x=-13+7/6
x=-6/6
x=-1

x=-13-7/ 6
x=-20/6 or 3.3repeating

3x²+14x+15=0
x=-14±√14²-4(3)(15) / 2(3)
x=-14±√196-180 /6
x=-14±√16 / 6

x=-14+4/6
x=-10/6 or 1.6repeating

x=-14-4/6
x=-18/6
x=-3

User ISeeker
by
6.9k points